Abnormalities in Blood Parameters in Athletes Taking Anabolic Androgenic Steroidal Agents; an Observational Clinical Study - Mubarak GS; Bamagous GA; Alsanosi SM; Alhindi YZ; Alqashqari HS; Albar HT; Siddiqi AM; Ayoub N; Falemban AH (Substance Abuse and Rehabilitation)
Ghaida Siraj Mubarak,1 Ghazi A Bamagous,2 Safaa M Alsanosi,2 Yosra Z Alhindi,2 Hamsah S Alqashqari,3 Halah Tariq Albar,4 Ahmed M Siddiqi,5 Nahla Ayoub,2 Alaa H Falemban2 1Pharmacy Department, Hera’ General Hospital, Ministry of Health, Makkah, Saudi Arabia; 2Department of Pharmacology and Toxicology, Faculty of Medicine, Umm Al Qura University, Makkah, Saudi Arabia; 3Department of Community Medicine and Pilgrims Health Care, Faculty of Medicine, Umm Al Qura University, Makkah, Saudi Arabia; 4Department of Physiology, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 5Department of Internal Medicine, National Guard Hospital, Jeddah, Saudi ArabiaCorrespondence: Alaa H Falemban, Email ahfalemban@uqu.edu.saBackground: Many studies indicate that high and multiple doses of anabolic-androgenic steroids (AAS) for athletic enhancement can result in serious and irreversible adverse effects. A study that includes laboratory blood testing to evaluate the direct effects of AAS agents among users has not been previously undertaken. The purpose of this study was to investigate the adverse effects of the use of AAS by athletes and to determine whether AAS use leads to changes in certain blood parameters.Methods: This is an observational study consisting of two stages. First, the participants completed an online questionnaire assessing sociodemographic characteristics, and knowledge and attitudes towards AAS. Second, volunteers underwent laboratory blood testing. Analysis was conducted using frequency distributions and percentages of responses across various variables.Results: Thirty-one individuals completed the online questionnaire, 18 of whom continued to stage 2, where blood samples were taken to trace any changes in blood parameters. All the participants were male, with an age range of 24– 45 years. The results showed that 94% of the participants used AAS for nontherapeutic purposes. Most participants reported that they take a combination of AAS (96%), as well as in combination with other supplements (74%). The most used combination was testosterone plus growth hormone (45%), and the most used supplements were liver protectors (84%). Seventy-four percent of the participants reported side effects, and 28% had received a medical diagnosis, such as hypertension, hyperlipidemia or an infertility. High levels of testosterone, prolactin, alanine transaminase (ALT), aspartate transferase (AST) and lipid profile, and low luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were observed.Conclusion: The unsupervised use of AAS alone or in combination with other hormones and/or supplements may lead to adverse effects. Further studies with larger samples are needed to draw significant conclusions about the safety of using AAS.Keywords: anabolic steroids, gym, male, abuse, testosterone, side effect